2023
DOI: 10.3389/fcvm.2023.1193878
|View full text |Cite
|
Sign up to set email alerts
|

Case report: State-of-the-art risk-modifying treatment of sudden cardiac death in an asymptomatic patient with a mutation in the SCN5A gene and a review of the literature

Petar Brlek,
Eduard Stjepan Pavelić,
Jana Mešić
et al.

Abstract: Brugada syndrome is a rare hereditary disorder characterized by distinct ECG findings, complex genetics, and a high risk of sudden cardiac death. Recognition of the syndrome is crucial as it represents a paradigm of sudden death tragedy in individuals at the peak of their lives. Notably, Brugada syndrome accounts for more than 20% of sudden cardiac deaths in individuals with structurally normal hearts. Although this syndrome follows an autosomal dominant inheritance pattern, it is more prevalent and severe in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…WGS presently facilitates precise diagnostics of rare diseases in cases such as uniparental isodisomy among children with Prader-Willi and Angelman syndromes, de novo deep intronic variants, and repeat expansions in non-coding regions among individuals affected by diseases such as myotonic dystrophies. Moreover, our experience extends to cases where traditional diagnostic approaches failed to provide conclusive results [128,129]. The synergy of genomics, metabolomics, and proteomics has been instrumental in uncovering elusive genetic mutations and intricate molecular signatures that would have otherwise gone undetected.…”
Section: Clinical Experiences With Ngs Diagnosticsmentioning
confidence: 89%
“…WGS presently facilitates precise diagnostics of rare diseases in cases such as uniparental isodisomy among children with Prader-Willi and Angelman syndromes, de novo deep intronic variants, and repeat expansions in non-coding regions among individuals affected by diseases such as myotonic dystrophies. Moreover, our experience extends to cases where traditional diagnostic approaches failed to provide conclusive results [128,129]. The synergy of genomics, metabolomics, and proteomics has been instrumental in uncovering elusive genetic mutations and intricate molecular signatures that would have otherwise gone undetected.…”
Section: Clinical Experiences With Ngs Diagnosticsmentioning
confidence: 89%
“…While the FHIHD feature provided a high-level understanding of a patient's family history and whether they had any heart-related conditions, it only offered a limited view of the patient's generational tree. Recent studies have revealed that sudden cardiac deaths have occurred in completely asymptomatic individuals who carried pathogenic variants in genes linked to sudden cardiac death [42]. However, this study did not collect any genetic data, which was another limitation.…”
Section: Limitationsmentioning
confidence: 94%
“…Brugada syndrome (BrS) exhibits a relatively low incidence, estimated to be less than 1% of the population. However, despite its infrequency, this syndrome accounts for more than 10% of all cases of sudden death and can be responsible for up to 20% of sudden deaths in individuals with structurally normal hearts [ 2 ]. Notably, BrS demonstrates a clear male predominance, with an approximate male-to-female ratio of 8:1.…”
Section: Main Textmentioning
confidence: 99%